2007
DOI: 10.4028/www.scientific.net/kem.353-358.178
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Characteristics of Vulcanized Natural Rubber for Automotive Engine Mounting

Abstract: In order to investigate fatigue characteristics of vulcanized natural rubber (NR), fatigue tests are carried out under various stress ratios R (R = minimum stress / maximum stress). It was considered that the fatigue cracks were initiated from flaws in very early stage of total life. The fatigue damage process was almost the fatigue crack propagation process and it is independent of R. The crack growth rate was proportional to the crack length to about the first power, when the crack length was defined as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…• For k 2 ½1 ; 1:259, the ranking is given by equation 7 • Finally, for k > 2:9 ( Figure 1) the ranking is given by equation 10as e AÀE he log he eng he O he GÀL (10) Generally, all the strain measures, described above, can be considered as damage parameters to estimate the fatigue life of rubbers. The difference existing between the various types of strain measures leads to various fatigue predictions for rubbery materials.…”
Section: Strain-based Damage Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…• For k 2 ½1 ; 1:259, the ranking is given by equation 7 • Finally, for k > 2:9 ( Figure 1) the ranking is given by equation 10as e AÀE he log he eng he O he GÀL (10) Generally, all the strain measures, described above, can be considered as damage parameters to estimate the fatigue life of rubbers. The difference existing between the various types of strain measures leads to various fatigue predictions for rubbery materials.…”
Section: Strain-based Damage Parametersmentioning
confidence: 99%
“…This justifies the use of the maximum of the predictive quantities, whatever the nature of the fatigue predictor, when dealing with the uniaxial or multiaxial fatigue of rubbers. 126 As we focus on the uniaxial fatigue life of the SBR rubber, only the strain damage parameters are investigated. Subsequently peak parameters εk,M will be examined.…”
Section: Finite Element Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Existing researches accounting for strain ratios or other relevant factors usually establish equivalent strainlike or energy-like damage parameters based on the crack initiation method or crack propagation method. [13][14][15][16][17][18] Cadwell et al 13 initially demonstrated that the fatigue life of natural rubber is a function of both the minimum engineering strain and engineering strain range. Oshima et al 14 used a Haigh diagram to predict fatigue life of a rubber mount with different stress mean and stress amplitude.…”
Section: Introductionmentioning
confidence: 99%
“…Rubber (Hevea brasiliensis Mull-Arg.) plantations are a source of natural rubber, a versatile material that is important to humans for daily life (Ngolemasango et al, 2008;Palosuo et al, 1998;Shibata et al, 2007). There is a constant demand for natural rubber globally: 12.27 million tonnes in 2014, which increased to 13.91 million tonnes in 2019, an average increment of 0.33 million tonnes/ year (Office of Agricultural Economics, 2020).…”
Section: Introductionmentioning
confidence: 99%